Basophilic method for lanthanide MOFs with a drug ligand: Crystal structure and luminescence - Yan, Z.Q.; Meng, X.T.; Su, R.R.; Zeng, C.H.; Yang, Y.Y.; Zhong, S.; Ng, S.W. (Elsevier, 2015)
Recently developed basophilic method was adopted to synthesize phenolic hydroxyl bridged lanthanide MOFs (Ln-MOFs) 1 and 2, based on a drug ligand of salicylic acid. 1 and 2 have the general formula of [Ln(HL1)L1·H2O]n (H2L1 = salicylic acid, Ln = Tb and Gd), they are characterized by X-ray single crystal diffraction, fourier transform infrared (FT-IR), elemental analysis (EA), thermogravimetric analysis (TGA) and powder X-ray diffraction (PXRD). It is found that the Ln Ln distance will be shorter if more phenolic hydroxyl as bridges, this will lead to more rigid framework and suggesting that the hydroxyl bridged CPs are good candidates for photophysical and magnetic materials. Furthermore, the luminescence property of 1 was investigated.